2019
DOI: 10.1101/808899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pseudo-repeats in doublecortin make distinct mechanistic contributions to microtubule regulation

Abstract: Doublecortin (DCX) is a neuronal microtubule-associated protein (MAP) indispensable for brain development. Its flexibly linked DC domains -NDC and CDC -mediate microtubule (MT) nucleation and stabilisation, but it is unclear how. Using high-resolution time-resolved cryo-EM, we mapped NDC and CDC interactions with tubulin at different MT polymerisation stages and studied their functional effects on MT dynamics using TIRF microscopy. Although coupled, each DC repeat appears to have a distinct role in MT nucleati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 64 publications
(112 reference statements)
0
23
0
Order By: Relevance
“…Within the microtubule-binding region of DCLK1 (aa 44-263), we found that 9 sites were more frequently phosphorylated in DCLK1-WT samples and 17 sites were more frequently phosphorylated in DCLK1-ΔC samples ( Figure 3A-B). Of the 17 phosphorylation sites in DCLK1-ΔC, 5 either directly contact tubulin or are adjacent to residues that directly contact tubulin within the lattice (42). The architecture of DCLK1 suggests it likely has the flexibility to autophosphorylate its N-terminal half due to an intrinsically disordered region between the DC2 domain and the kinase domain ( Figure 3C, aa 263-374).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Within the microtubule-binding region of DCLK1 (aa 44-263), we found that 9 sites were more frequently phosphorylated in DCLK1-WT samples and 17 sites were more frequently phosphorylated in DCLK1-ΔC samples ( Figure 3A-B). Of the 17 phosphorylation sites in DCLK1-ΔC, 5 either directly contact tubulin or are adjacent to residues that directly contact tubulin within the lattice (42). The architecture of DCLK1 suggests it likely has the flexibility to autophosphorylate its N-terminal half due to an intrinsically disordered region between the DC2 domain and the kinase domain ( Figure 3C, aa 263-374).…”
Section: Resultsmentioning
confidence: 99%
“…Although originally hypothesized to be DC1, subsequent structural and biochemical studies called into question the identity of the bound DC domain (44,45). A recent cryo-EM study has proposed that DC2 binds to the newly polymerized GTP microtubule lattice, while DC1 binds the mature GDP microtubule lattice (42). All of our binding assays are performed with taxol-stabilized microtubules in the GDP state (46); however, based on our phosphorylation data, we reasoned that DC2 could still contribute to efficient binding of DCLK1 to GDP microtubules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interaction with microtubules differs dramatically between TgDCX and its orthologues, also likely differs between TgDCX and human doublecortin. In the case of doublecortin, a detailed model of the interaction of its two DCX domains (NDC and CDC) with microtubules has been proposed, based on high-resolution structural information from cryoEM [32]. A striking feature of the model is that for the most part, binding of the two domains to the microtubule is mutually exclusive: either NDC binds or CDC binds, with differing consequences for microtubule architecture, but apparently the two domains rarely or never bind simultaneously.…”
Section: Discussionmentioning
confidence: 99%